Assessment of Pediatric Residents' Comfort Level With CellScope Oto to Examine Pediatric Ear Exams. (July 2022) - Smola, Cassi; Shah, Nipam; Fowler, Andrew; Gubbels, Alexandra; Monroe, Kathy
Examining a child's tympanic membrane (TM) is challenging, but crucial for proper management of acute otitis media (AOM). CellScope Oto (CSO) is an attachment that turns a smartphone into an otoscope. We aimed to assess pediatric resident comfort level with ear exams using CSO to see whether comfort level and accuracy of diagnosis of AOM improved. A pre-post study of pediatric residents in a freestanding Pediatric Emergency Department was conducted to assess their comfort level of traditional otoscope and CSO via a Likert scale. Ear exams were recorded and rated by 2 faculty for accuracy of AOM diagnosis. A total of 18 pediatric residents participated, and 308 exams were collected, with 2% diagnosed as AOM. The median change in comfort level increased by +1.0 for interns and third years but remained unchanged for second years. There was substantial agreement by faculty raters of video ear exams. Overall, comfort level increased with accuracy of diagnosis of AOM.